2018
DOI: 10.1016/j.nedt.2018.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of undergraduate educational environment in medical and nursing program using the DREEM tool

Abstract: Both medical and nursing students appreciated the EE pertaining to Perception of Learning (PoA), Academic Self- Perception (ASP), Perception of learning (PoL) and Social Self-perception (SSP). The study showed that nursing students' perception on their EE was relatively more satisfactory than medical students. However, both medical and nursing students identified areas of improvement in the domain of Perception of Teaching (PoT). This finding indicates dire need to devise innovative teaching strategies both fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
5
15
0
Order By: Relevance
“…The score in this category of 31.13±4.9 in our study places it in the 'Moving in the right direction' category. A result from IMU is 30.50 which is within the same range while a study from result from Pakistan reported a score of 24.0 (± 5.0) in this domain (Farooq et al, 2018;Lai et al, 2009). In our study, there was statistically significant difference (p <0.05) in the mean scores between pre-clinical and clinical students with the clinical students score being higher, although both scores remain in the same category.…”
Section: Students' Perceptions Of Teachingmentioning
confidence: 60%
“…The score in this category of 31.13±4.9 in our study places it in the 'Moving in the right direction' category. A result from IMU is 30.50 which is within the same range while a study from result from Pakistan reported a score of 24.0 (± 5.0) in this domain (Farooq et al, 2018;Lai et al, 2009). In our study, there was statistically significant difference (p <0.05) in the mean scores between pre-clinical and clinical students with the clinical students score being higher, although both scores remain in the same category.…”
Section: Students' Perceptions Of Teachingmentioning
confidence: 60%
“…The learning environment can have a lasting impact on the knowledge, critical reasoning, and motivation of the students. It serves as a key indicator for evaluating the curriculum and learning experiences of students where their satisfaction indicates the quality of an educational program [ 52 55 ]. This study revealed a significant improvement in the learning environment for almost all items studied, with the largest percentage point increases in the availability and effectiveness of instructors.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of the learning environment in the nursing student participants of this study is more positive than negative, as in many studies where this tool was used [15,35,54,[60][61][62][63][64][65][66][67][68]. So far, only one study has been conducted that provides researchers with insight into the differences between personal and online teaching.…”
Section: Discussionmentioning
confidence: 99%